Isolation and characterization of two vitellins from eggs of the spider Polybetes pythagoricus (Araneae: Sparassidae) - Laino, Aldana (2011)
Despite vitellins being essential yolk proteins, their presence in spiders remains almost unknown. Two vitellins from the spider Polybetes pythagoricus, named LV1 and LV2, were isolated and their size, shape, lipids, fatty acids, proteins and carbohydrates moieties were determined. LV1 has a density similar to that of HDL with 49.3% lipids, and LV2 has a density similar to that of VHDL with 9.7% lipids. The major neutral lipid present in both vitellins was found to be esterified cholesterol, 16% for LV1 and 24% for LV2. The major fatty acid was 18:1n-9 in LV1 and LV2. Results from native PAGE showed a lipoprotein of 550 kDa for LV1 and three lipoproteins of 571, 400 and 257 kDa for LV2. SDS-PAGE evidenced two major apolipoproteins of 64 and 25 kDa in LV1. The three lipoproteins of LV2 were electroeluted and analyzed by SDS-PAGE, showing different proportions of the same apolipoproteins (181, 67 and 60 kDa). LVs were analyzed by spectrophotometry, immunochemical and electron microscopy, showing that the respiratory pigment hemocyanin was not present as apolipoprotein. This fact evidenced that these LVs were not related to hemolymphatic lipoproteins.